R-Wave Singularity: A New Morphological Approach to the Analysis of Cardiac Electrical Dyssynchrony - Zhan, Ping; Li, Tao; Shi, Jinlong; Wang, Guojing; Wang, Buqing; Liu, Hongyun; Wang, Weidong (Frontiers in Physiology, 2020)
R-wave singularity (RWS) measures the intermittence or discontinuousness of R waves. It has been broadly used in QRS detection, ECG beats classification, etc. In this paper, we novelly developed RWS to the analysis of QRS morphology as the measurement of ventricular dyssynchrony and tested the hypothesis that RWS could enhance the discrimination between control and atute myocardial infarction (AMI) patients. Holter ECG recordings were obtained from the Telemetric and Holter ECG Warehouse (THEW) database, among which database Normal was extracted as normal controls (n=202) and database AMI (n=93) as typical subjects of autonomic nervous system (ANS) dysfunction with high risk for cardiac arrhythmias and sudden cardiac death. Experimental results demonstrate that RWS measured by Lipschitz exponent (LE) calculated from 5-min Holter recordings was significantly higher in AMI_1 and AMI_2 subjects than that in Normal subjects for overall, elderly and elderly male groups, which suggested the heterogeneous depolarization of the ventricular myocardium during AMI. Receiver operating characteristic curve analyses show that combined with heart rate variability parameters, LE provides higher accuracy in distinguishing between the patients with AMI and healthy control subjects for overall, elderly, elderly male and elderly female groups. In summary, our study demonstrates the significance of using RWS to probe the cardiac electrical dyssynchrony for AMI. LE may be valuable and complementary for existing cardiac resynchronization therapy and ANS assessment.